Safety culture, quality of care, missed care, nurse staffing and their impact on pressure injuries: A cross-sectional multi-source study - Faisal Khalaf Alanazi; Samuel Lapkin; Luke Molloy; Jenny Sim (Elsevier, 2023)
Background: Safety culture is known to influence patient outcomes, but the relationship between nursing units' safety cultures and the development of pressure injuries in acute care hospitals is unclear. Pressure injuries are a nursing-sensitive patient outcome and are widely considered preventable. Objective: To examine the impact of unit safety culture, nursing unit characteristics, and missed care on pressure injury rates in Saudi Arabian hospitals. Design: A multi-center cross-sectional study was conducted between August and November 2021 and compared to secondary data on the incidence of pressure injuries. Settings/Participants: A total of 653 nurses from 35 units in five Ministry of Health hospitals in Saudi Arabia participated in this study. Methods: The survey included validated scales of safety culture, nurse staffing, and nurses' perceptions of quality of care, missed care, and the frequency of pressure injury. Secondary data on pressure injuries were collected from the Ministry of Health administrative database between 2018 and 2021. Descriptive analysis and Generalized Linear Models were performed. Results: Higher safety culture scores were associated with fewer pressure injuries (β = -2.000, 95% Confidence Interval [CI] -3.107, -0.893) and lower nurses' perceptions of the frequency of pressure injuries in their unit (β = -1.224, 95% CI -2.255, -0.192). High scores on the sub-scales of hospital management (β = -2.105, 95% CI -2.835, -1.375) and safety climate (β = -1.402, 95% CI -2.383, -0.421) were the most statistically significant predictor for pressure injury prevention. Higher frequency of missed nursing care was positively associated with higher rates of pressure injuries (β = 1.606, 95% CI 0.187, 3.024) and higher nurses' perceptions of the frequency of pressure injuries (β = 1.243, 95% CI 0.211, 2.363). There was a positive relationship between higher nurses' perceptions of the frequency of pressure injury and higher incidence rate of pressure injury as reported in the incident management system (β = 1.183, 95% CI 0.065, 2.301). Conclusion: Nursing units with stronger safety climate and safety behavior scores, higher ratings of hospital and unit quality of care, and lower levels of missed nursing care were associated with lower incidence of pressure injury and nurses' perceptions of the frequency of pressure injury in their units. Nurses' perceptions of the frequency of pressure injuries are concordant with the incidence of pressure injuries and can be a valid measure to capture patient outcomes within a specific time. Tweetable abstract: High safety culture and lower missed care are linked to fewer pressure injuries in Saudi Arabian hospitals. Nurses' perceptions of pressure injury frequency aligned with reported incidence rates, indicating a valid measure of patient outcomes.